2022
DOI: 10.3389/fchem.2022.994721
|View full text |Cite
|
Sign up to set email alerts
|

Phyto-fabrication of silver nanoparticles and their catalytic dye degradation and antifungal efficacy

Abstract: The biogenic synthesis of silver nanoparticles (AgNPs) and their potent application against dye degradation and phytopathogens are attracting many scientists to nanotechnology. An attempt was made to synthesize silver nanoparticles using Plantago ovata leaf extract and test their effectiveness in removing organic dyes and antifungal activity. In the present study, stable AgNPs were synthesized from 0.1 mM AgNO3 and authenticated by observing the color change from yellow to red-brown, which was confirmed with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 82 publications
1
8
0
Order By: Relevance
“…The rate constant for the degradation reaction was 0.01083 mM −1 s −1 . Many of the literature reports indicated that the degradation of methylene blue by biogenic silver nanoparticles fitted pseudo first-order kinetics [62,70,71]. In our study, plotting ln A t /A o versus time yielded a straight line whose linear relationship was y = −0.0069x − 0.3598; R 2 = 0.9703.…”
Section: Agnps Catalyzed Degradation Of Methylene Blue Dyesupporting
confidence: 57%
“…The rate constant for the degradation reaction was 0.01083 mM −1 s −1 . Many of the literature reports indicated that the degradation of methylene blue by biogenic silver nanoparticles fitted pseudo first-order kinetics [62,70,71]. In our study, plotting ln A t /A o versus time yielded a straight line whose linear relationship was y = −0.0069x − 0.3598; R 2 = 0.9703.…”
Section: Agnps Catalyzed Degradation Of Methylene Blue Dyesupporting
confidence: 57%
“…The AgNPs synthesis was found dependent on the addition of a reducing agent ( Salvia extract) in AgNO 3 solution, which resulted in a colourimetric change from pale yellow to reddish-brown. However, increase in the quantity of reducing agent led to the rapid AgNPs synthesis and eventually agglomeration, which is depicted from the noisy and bathochromic SPR band [ 28 , 32 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…This reveals that the slightly alkaline pH is favorable for NPs biosynthesis. However, pH values (greater than 9) reduces the NPs synthesis and stability [ 32 , 36 , 37 ]. Determining temperature effect (r.t, 40 °C, 50 °C, 60 °C, 70 °C, 80 °C, 80 °C, and boiling), the UV–Vis spectral graphs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The MB absorbance remained largely unchanged, indicating weak degradation activity when no photocatalyst was present, as observed during photodegradation under both UV and solar irradiation in blank conditions. Githala 44 found that the phyto-fabrication of silver nanoparticles showed the breaking down of organic dyes such as MB and Congo red, effectively inhibiting the fungal growth of A. alternata .…”
Section: Resultsmentioning
confidence: 99%